Synthesis and Characterization of N,N',N'-Trichloro-6,7-epoxy-o-MeO-cinnamaldehyde Semicarbazone: A Potent Decontaminating Agent for Toxic Compounds - Ibomcha Singh, Soram; Prabha, Shashi (Asian Journal of Chemistry, 2015)
A series of novel substituted cinnamaldehyde derivatives were designed and successively synthesized in three steps starting from o-methoxy-cinnamaldehyde semicarbazone to epoxy and finally to the N-chloro derivatives respectively, on the basis of semicarbazone based chemical decontaminants model to meet the structural requirements necessary for decontamination activity. Epoxidation with t-BuOOH in alkaline condition and chlorination using calcium hypochlorite were carried out. The structures of the synthesized compounds were confirmed on the basis of IR, Mass, 1H NMR spectral analysis. The presence of o-methoxy moiety in the system might play a significant role in the reactivity of the compound as a whole. It is well known that chloramines possess strong decontamination properties against toxic compounds and warfare agents. A more in-depth biological and chemical evaluation of the synthesized chloramine derivative(s) on toxic compounds of phosphorus and chemical warfare agents under suitable conditions requires a highly sophisticated laboratory.